State-Society Synergy for Accountability : Lessons for the World Bank. (World Bank working paper, 2004)
"The central question guiding this study is: How can the relationship between the state and society be transformed from a process of particularistic demands into a healthier engagement that produces policy outcomes serving the public interest?"